Strengthening Qur'anic Literacy through Ma'had Al-Jami'ah Programs: A Mixed-Methods Evaluation in Islamic Higher Education - Ade Mas'ud; Devi Jusma Nur; Natasya Bahmid; Degha Aulia Pattuju; Aminah Sulanto (Postgraduate Program of the State Islamic Institute of Palopo, 2025)
Qur’anic literacy remains a fundamental component of Islamic education and an essential competency for students in Islamic higher education institutions. However, variations in students’ Qur’anic reading abilities continue to present challenges for universities seeking to strengthen both academic and religious competencies. This study aims to evaluate the effectiveness of the Qur’anic literacy development programs implemented by Ma’had Al-Jami’ah at IAIN Palopo. Employing a mixed-methods approach with a convergent descriptive design, the study involved 68 students from the Islamic Educational Management Study Program selected through proportional sampling. Data were collected through questionnaires, interviews, and document analysis and were analyzed using descriptive statistics and qualitative data analysis techniques. The findings reveal that the Qur’anic literacy development programs are implemented through three integrated components: Tahsinul Qira’ah courses, Character Building Training (CBT), and special mentoring sessions for students requiring additional support. Students generally perceived the programs positively, with the largest proportion of respondents (39.71%) categorizing the programs as highly effective. Furthermore, learning achievement data showed that the dominant grade in the Tahsinul Qira’ah course was B+ across both student cohorts, indicating satisfactory academic performance. The integration of perceptual and achievement-based evidence suggests that the programs are effective in strengthening students’ Qur’anic literacy. This study contributes to Islamic educational evaluation by proposing a comprehensive assessment framework that combines students’ perceptions and learning outcomes as complementary indicators of program effectiveness. The findings highlight the strategic role of Ma’had Al-Jami’ah in fostering religious competencies and supporting holistic student development within Islamic higher education.